The visual stimulus in global ceramics during the period of modernism: Transformations of form and aesthetic signification - Zeena Kasem Mohammed; Rula Abdul-Ilah Alwan Al-Nuaimi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The present study investigates the notion of the visual stimulus in global ceramics during the modernist era, with particular emphasis on the transformations of form and aesthetic signification that emerged within ceramic practice under the influence of the artistic and intellectual movements accompanying modernity. It has become evident that the developments in ceramics during this period were not confined to technical or formal innovations; rather, they embodied profound shifts in visual and aesthetic conceptualization. Ceramics evolved from a functional and decorative medium into a visual and philosophical discourse, undergoing transformations that extended beyond the external configuration to encompass the deeper layers of meaning inherent in the art form. This entailed an interplay between the visual and the sensory, wherein the ceramic composition was no longer a mere traditional arrangement but was reconstituted as an aesthetic and visual statement. Such transformations were facilitated by the engagement of ceramic practice with diverse modernist artistic and intellectual schools, including abstraction, cubism, conceptual art, and Dadaism. These tendencies engendered a new visual language within ceramics, one that addresses the viewer on multiple cognitive and perceptual levels, inviting a reconsideration of the dynamic relationship between form and content.The research is structured into four chapters. The first chapter outlines the general framework, presenting the research problem which culminates in the central inquiry: In what ways did the visual stimulus in global ceramics during the modernist era contribute to transformations in form and aesthetic signification? This is followed by the significance of the study, its objectives aimed at identifying the visual stimulus in global ceramics during modernity in relation to formal and aesthetic transformations, together with the delimitation of the study (thematic, temporal, and spatial), and the definition of key terms. The second chapter, the theoretical framework, comprises two sections: the first examines the concept of the stimulus, while the second explores ceramics through the lens of modernist art movements: focusing on the transformations of form and aesthetic signification. This chapter further identifies the indicators derived from the theoretical framework and reviews relevant prior studies. The third chapter is devoted to methodological procedures and the analysis of selected samples, while the fourth chapter presents the results, their discussion, conclusions, recommendations, and suggestions, followed by the list of references.Among the principal findings:Ceramic artists engaged in producing modernist compositions that embodied visual stimuli transcending traditional frameworks. Through the deployment of optical strategies, they generated unfamiliar configurations such as the fusion of organic and mechanical forms, that stimulate visual perception and provoke inquiry into the origins and functions of form. This process situates the viewer within a state of profound contemplation and heightened sensory responsiveness.DOI: https://doi.org/10.54633/2333-024-057-019